The Function of Taboo Expressions in Nicki Minaj’s Song Lyrics - Anindita Dewangga Puri; Theodora Pramasitha Yudanti; Owena Zaneta Yogaswari (Journal of Language and Literature, 2024)
The societal phenomenon of taboo terms is commonly expressed in song lyrics. This research focuses on the function of taboo expressions in the song lyrics of Nicki Minaj, a singer who is known to use such expressions. The first objective of this analysis is to determine the types of taboo expressions found in Minaj’s songs. Secondly, the researchers examine the function of these expressions in the song lyrics. Four of Minaj's songs are presented in the data: "Superbass," "Megatron," "Barbie Tingz," and "Anaconda." This research employs descriptive and qualitative analysis, as well as the theoretical frameworks provided by Battistella (2005) and Wardhaugh (2021). The findings demonstrate that vulgarity is the most frequent form of taboo expression in Minaj's song lyrics, while the main function of these phrases is to attract attention. These songs indicate more than simply linguistic qualities; they also offer a thorough understanding of the social setting. This study fills a gap in the literature on taboo expressions in song lyrics by revealing the function and types of taboo expressions employed by a well-known singer. This research has the capacity to enlighten future research on the usage of taboo expressions in music, and the broader cultural consequences of such language implication.